Reconstructing the Meaning of Abstention as a Form of Political Participation in Democratic States - Sulistyowati Sulistyowati; Suryadi Suryadi; Gusti Bintang Maharaja; Bagas Octa Pribakti (Annals of Justice and Humanity, 2026)
This study aims to reconstruct the meaning of the Golongan Putih (Golput) phenomenon in Indonesia and to examine its position within democratic theory and constitutional law. The research employs a normative-juridical method combined with a qualitative literature review. Data were collected by examining the 1945 Constitution of the Republic of Indonesia, election laws and regulations, scholarly articles, books, election reports, and relevant studies on political participation. The analysis was conducted using historical, conceptual, and constitutional approaches, supported by the theoretical frameworks of Albert O. Hirschman’s Exit, Voice, and Loyalty, Pippa Norris’s Critical Citizenship, and Jürgen Habermas’s Legitimation Crisis. The findings reveal that Golput should not be understood merely as political apathy or civic disengagement. Rather, it often represents a conscious form of political protest, a rational response to dissatisfaction with political representation, and an alternative mode of participation in a democratic public sphere. The study concludes that abstention can function as an important corrective signal for democratic systems experiencing declining public trust and legitimacy. However, this research is limited by its reliance on normative legal analysis and secondary data, without empirical field surveys or direct interviews with abstaining voters. The study contributes to the development of constitutional law, political sociology, and democratic governance studies by offering a broader understanding of electoral abstention as a legitimate political expression and by encouraging a shift from procedural democracy toward a more substantive, deliberative, inclusive, and socially just democratic framework.